Root physiological traits and cold hardiness of alfalfa grown alone or mix-sowed with meadow fescue. (3rd April 2017) - Shen, Xiaohui; Li, Jiandong; Feng, Peng; Jiang, Cheng; Li, Rulai; Zhang, Hua; Jia, Huibin; Zheng, Haiyan; Zhu, Baoguo
ABSTRACT: Cold hardiness is important for alfalfa ( Medicago sativa L.) grown in northeast China. We investigated overwintering for three alfalfa grown alone or mix-sowed with meadow fescue. During the overwinter stage of the year from October 2013 to April 2014, five physiological and biochemical indexes and overwintering rate were investigated under natural conditions. The results showed that no matter either singly sowed or mix-sowed plants, physiological traits such as soluble sugar, soluble protein, and free proline of the alfalfa roots increased as the temperature decreased at the end of autumn, and decreased when the air temperature increased in the spring. The malondialdehyde content and peroxidase activity of all the treatments showed the trend of up–down–up during the whole overwintering stage. Investigation of the overwintering rate and using the membership function method combined with correlation analyses revealed that the order of the cold resistance of the selected alfalfa cultivars was as follows: Gongnong1 + meadow fescue > Gongnong1 > Wega7F + meadow fescue > Wega7F > WL319HQ + meadow fescue > WL319HQ. These results indicated that the cold resistance of alfalfa mix-sowed with the meadow fescue was higher than that of alfalfa that was singly sown.